Influence of ABCB11 and HNF4α genes on daclatasvir plasma concentration: preliminary pharmacogenetic data from the Kineti-C study - Cusato, Jessica; De Nicolò, Amedeo; Boglione, Lucio; Favata, Fabio; Ariaudo, Alessandra; Mornese Pinna, Simone; Guido, Federica; Avataneo, Valeria; Carcieri, Chiara; Cariti, Giuseppe; Di Perri, Giovanni; D’Avolio, Antonio (Journal of antimicrobial chemotherapy, 2017)
Daclatasvir is an inhibitor of HCV non-structural 5A protein and is a P-glycoprotein substrate. Pharmacogenetics has had a great impact on previous anti-HCV therapies, particularly considering the association of IL-28B polymorphisms with dual therapy outcome. We investigated the association between daclatasvir plasma concentrations at 2 weeks and 1 month of therapy and genetic variants (SNPs) in genes encoding transporters and nuclear factors (ABCB1, ABCB11 and HNF4α). Allelic discrimination was achieved through real-time PCR, whereas plasma concentrations were evaluated through LC-MS/MS. Fifty-two patients were analysed, all enrolled in the Kineti-C study. HNF4α 975 C > G polymorphism was found to be associated with the daclatasvir plasma concentrations at 2 weeks (P = 0.009) and 1 month of therapy (P = 0.006). Linear regression analysis suggested that, at 2 weeks of therapy, age, baseline BMI and haematocrit were significant predictors of daclatasvir concentrations, whereas at 1 month of therapy ABCB111131 CC and HNF4α CG/GG genotypes were significant predictors of daclatasvir concentrations. These are the first and preliminary results from our clinical study focusing on daclatasvir pharmacogenetics, showing that this approach could have a role in the era of new anti-HCV therapies.